Prognostic significance of the digit ratio after hormone therapy for prostate cancer: a prospective multicenter study - Guanjian Li (Nature Portfolio, 2017)
Abstract The digit ratio has been used as a retrospective noninvasive biomarker to investigate the putative effects of prenatal exposure to androgens. In recent years, many scholars have paid attention to the association between 2D:4D (the second and fourth digits) and prostatic cancer. This study explored the prognostic significance of digit ratio in prostate cancer patients. We reviewed the progressive status and survival of 382 prostate cancer patients who had received hormone therapy at our institutions. Survival of clinicopathological variables analyzed as categorical variables were determined by the log-rank test. According to Cox’s proportional hazards analysis, R2D:4D, L2D:4D, PSA at 6 month,bone metastasis were significant independent factors for prostate cancer. The risk of any progression of prostate cancer similarly depressed with increasing 2D:4D, for any progression (R2D:4D HR = 0.71, p = 0.003; L2D:4D HR = 0.67, p = 0.001), for cancer-specific death (R2D:4D HR = 0.67, p = 0.025; L2D:4D HR = 0.74, p = 0.036). Digit ratio may not only have predictive value in risk but also prognosis of prostatic cancer. This finding suggests that low 2D:4D can be used as prognostic factors to identify patients with a poor prognosis. These patients may benefit from more aggressive management.